White-Tailed Deer Habitat : Ecology and Management on Rangelands - Fulbright, Timothy E. (Book collections on Project MUSE., 2013)
The first edition of this book was hailed as "a splendid reference for the classroom and those who make their living from wildlife and the land" and as "filling a niche that is not currently approached in the literature." In this second, full-color edition, revised and expanded to include the entire western United States and northern Mexico, the authors provide a carefully reasoned synthesis of ecological and range management principles. The topics discussed in this edition include rangeland vegetation management and the impact of crops, livestock, predation, and population density within the context of arid and semiarid habitats.